Diversity of RNA viruses of three dominant tick species in North China - Qin, Tong; Shi, Mingjie; Zhang, Meina; Liu, Zhitong; Feng, Hao; Sun, Yi (Frontiers in Veterinary Science, 2023)
A wide range of bacterial pathogens have been identified in ticks, yet the diversity of viruses in ticks is largely unexplored. Here, we used metagenomics sequencing to characterize the diverse viromes in three principal pathogens associated tick species, Haemaphysalis concinna, Dermacentor silvarum, and Ixodes persulcatus, in North China. A total of 28 RNA viruses were identified and belonged to more than 12 viral families, including single strand positive sense RNA virus (Flaviviridae, Picornaviridae, Luteoviridae, Solemoviridae and Tetraviridae), negative sense RNA virus (Mononegavirales, Bunyavirales and others) and double strands RNA virus (Totiviridae, Partitiviridae). Of these, Dermacentor pestivirus-like virus, Chimay-like rhabdovirus, taiga tick nigecruvirus, and Mukava virus are presented as novel viral species, while Nuomin virus, Scapularis ixovirus, Sara tick borne phlebovirus, Tacheng uukuvirus, Beiji Orthonairovirus had been established as human pathogens with undetermined natural circulation and pathogenicity. Other viruses include Norway mononegavirus 1, Jilin partitivirus, tick borne tetravirus, Pico-like virus, Luteo-like virus 2, Luteo-like virus 3, Vovk virus, Levivirus, Toti-like virus and Solemo-like virus and others involved with unknown pathogenicity to human and wild animals. As a conclusion, extensive virus diversity frequently occurs in Mononegavirales and Bunyavirales among the three tick species. Comparatively, I. persulcatus ticks had demonstrated significant higher viral species diversity than those of H. concinna and D. silvarum ticks. Our analysis supported that ticks are reservoirs for a wide range of viruses and suggested that the discovery and characterization of tick borne viruses would have implications for viral taxonomy and provide insights into tick-transmitted viral zoonotic diseases.